Supremo Tribunal Federal: uma análise dos impactos da filiação religiosa na confiança institucional - Santos, Luiza Giacon Abreu dos (Universidade Federal de São Carlos, 2023)
The objective of the research is to analyze the level of trust of the Brazilian population in the Federal Supreme Court (STF), seeking to identify whether religious affiliation grounds a standard of trust. Therefore, trust is the main concept mobilized in this study, based on previous research that indicated the variables with the greatest explanatory power for the act of trusting the Judiciary (CUNHA & OLIVEIRA, 2019; DEL PORTO, 2013; SALZMAN & RAMSEY, 2013, RUSSO et al., 2018) and the way in which religion can influence people's values and political behavior (BOHN, 2009; BOAS & SMITH, 2017; FERREIRA & FUKS, 2021; JUNIOR et al., 2018). To achieve our objective, we developed and analyzed a logistic regression model, based on data from the LAPOP culture and political values survey, from 2019. The research was funded by CNPq, via a Scientific Initiation grant. The main conclusion of the research is that although religious affiliation does not act as a significant predictor of trust in the Supreme Court, people's level of religiosity (regardless of religious affiliation) helps to explain trust in the Supreme Court, being the main predictor of this Confidence is the perception of fairness of the courts.
Federal Supreme Court: an analysis of the impacts of religious affiliation on institutional trust
Keywords: Supremo Tribunal Federal; Justiça procedimental; Confiança; Religião; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS